Upaya Meningkatkan Kemampuan Menelaah Struktur Teks Deskripsi Dengan Menerapkan Metode Inkuiri - Ngurah Artha Yoga (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2023)
Students' learning ability in studying structure and language in descriptive texts is still low. This is due to the teacher's inaccuracy in applying the learning method. The purpose of this research is to improve the quality of using good and correct Indonesian through the ability to examine the structure and language of descriptive texts by applying the inquiry method to class VII B students of Tabanan 3 Junior High School in the 2021/2022 academic year. This research is a classroom action research which consists of two cycles with 32 students. Data collection methods used, namely the observation method and the test method. Observation method was used to get data about students' attitudes and behavior and the learning process. The test method is used to obtain test data on students' ability to study the structure and language of the descriptive text. Data analysis method used is descriptive method. The results showed that the ability to study the structure and language of the descriptive text of class VII B State Junior High School 3 Tabanan in the 2021/2022 academic year after applying the inquiry method had increased. This can be seen in the students' completeness obtained in the pre-cycle, which is 46.87% with an average score of 65.31 in the first cycle, students complete with a percentage of 12.92% with an average value of 73.75. The increase from cycle I to cycle II was 19.70%, in cycle II all students had completed (100%) with an average score of 88.28. The increase in the score is a sign that the ability to study structure and language in the descriptive text of class VII B State Junior High School 3 Tabanan for the academic year 2021/2022 is getting better after applying the inquiry method. Based on the results of data analysis, it can be concluded that by applying the inquiry method students' abilities have increased significantly. Thus, it is recommended for Indonesian language teachers to apply the inquiry method in learning activities because it has been proven that the application of the inquiry method can improve students' abilities.